2022
DOI: 10.3389/fmicb.2022.871937
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing for Detection and Characterization of Phosphorothioate Modifications in Native DNA Sequences

Abstract: Bacterial DNA is subject to various modifications involved in gene regulation and defense against bacteriophage attacks. Phosphorothioate (PT) modifications are protective modifications in which the non-bridging oxygen in the DNA phosphate backbone is replaced with a sulfur atom. Here, we expand third-generation sequencing techniques to allow for the sequence-specific mapping of DNA modifications by demonstrating the application of Oxford Nanopore Technologies (ONT) and the ELIGOS software package for site-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, the genomes of several S. aureus jumbo bacteriophages that are presumed to be enriched for uracil-substituted DNA were sequenced on an ONT MinION but produced “sequence data that could not be interpreted” by Korn and others, suggesting that 5-hydroxymethyluracil and/or other deoxyuracil derivatives may produce detectable distortions in nanopore sequencing; the same samples were not sequenceable by standard short read methods until the authors prepared sequencing libraries using the uracil-insensitive polymerase PhusionU ( Korn et al, 2021 ). Finally, the Nookaew laboratory used nanopore sequencing for the detection of phosphorothioate (PS) linkages ( Wadley et al, 2022 ), which occur naturally in prokaryotes and archaea ( Wang et al, 2007 ) and are also commonly used as stabilizing linkages during oligonucleotide synthesis to protect against nuclease digestion ( Vosberg and Eckstein, 1982 ). Using their previously developed ELIGOS software tool, which identifies sites with high base calling error rates via comparative statistical tests between two samples ( Jenjaroenpun et al, 2021 ), they identified sites with statistically significant differences in base calling error rates between PS+ and PS- samples, extracted raw nanopore features with Nanopolish, and analyzed those features to determine PS signatures in Salmonella enterica genomes, noting that ionic current disturbances occur at known sites of PS linkages.…”
Section: Early Detection Of Nucleic Acid Modifications By Nanopore Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the genomes of several S. aureus jumbo bacteriophages that are presumed to be enriched for uracil-substituted DNA were sequenced on an ONT MinION but produced “sequence data that could not be interpreted” by Korn and others, suggesting that 5-hydroxymethyluracil and/or other deoxyuracil derivatives may produce detectable distortions in nanopore sequencing; the same samples were not sequenceable by standard short read methods until the authors prepared sequencing libraries using the uracil-insensitive polymerase PhusionU ( Korn et al, 2021 ). Finally, the Nookaew laboratory used nanopore sequencing for the detection of phosphorothioate (PS) linkages ( Wadley et al, 2022 ), which occur naturally in prokaryotes and archaea ( Wang et al, 2007 ) and are also commonly used as stabilizing linkages during oligonucleotide synthesis to protect against nuclease digestion ( Vosberg and Eckstein, 1982 ). Using their previously developed ELIGOS software tool, which identifies sites with high base calling error rates via comparative statistical tests between two samples ( Jenjaroenpun et al, 2021 ), they identified sites with statistically significant differences in base calling error rates between PS+ and PS- samples, extracted raw nanopore features with Nanopolish, and analyzed those features to determine PS signatures in Salmonella enterica genomes, noting that ionic current disturbances occur at known sites of PS linkages.…”
Section: Early Detection Of Nucleic Acid Modifications By Nanopore Se...mentioning
confidence: 99%
“…Using their previously developed ELIGOS software tool, which identifies sites with high base calling error rates via comparative statistical tests between two samples ( Jenjaroenpun et al, 2021 ), they identified sites with statistically significant differences in base calling error rates between PS+ and PS- samples, extracted raw nanopore features with Nanopolish, and analyzed those features to determine PS signatures in Salmonella enterica genomes, noting that ionic current disturbances occur at known sites of PS linkages. This study represents the first use of high throughput nanopore sequencing to detect modifications of the nucleic acid backbone ( Wadley et al, 2022 ).…”
Section: Early Detection Of Nucleic Acid Modifications By Nanopore Se...mentioning
confidence: 99%
“…A method using optical visualization of PT modifications in single DNA molecules has been developed, however, this method is not high-throughput and doesn’t provide base resolution detection [ 19 ]. More recently, a PT-site detection method using nanopore sequencing was reported for plasmid and bacterial genomic DNA (gDNA) [ 20 ]. A convenient and accurate method for detecting PT modifications is still greatly needed to determine and unravel the unprecedented phosphorothioate epigenomes.…”
Section: Introductionmentioning
confidence: 99%